Cervical Neurofibroma: Things to Think About Before Surgery - Hariharan R; Anjali Singh; Uma Hariharan; Sandeep Kumar (Research and Practice in Anesthesiology, 2024)
Neurofibromatosis (NF), are a group of hereditary diseases transmitted in an autosomal dominant fashion and characterized by a tendency to formation of ectodermal or mesodermal tissue tumours, possessing NF1 or NF2 gene mutation.